R Rancang Bangun Filter Air Cetak Untul Lab Hidrolika - Ida Zuraida; Harun Rasidi; Wattini Wattini; Nizar Nizar (Jurnal Poli-Teknologi, 2022)
Clean water is a basic requirement of the Hydraulics Laboratory for experimental/practical applications. Sometimes the water used has decreased in quality because it is often used repeatedly, making the water smelly and cloudy. Therefore it needs to be discarded or replaced. So that the use of clean water is not wasteful, a printed water filter is designed for the purpose of purifying and saving water use. The initial stage is to design, then make a printed water filter model without using water filter materials in general. The next stage is the function test, whether it is successful or not, able or not to purify the water. The test results are then re-evaluated until the highest percentage of functional success is obtained. The final stage of the research is to test the functionality and test samples. Testing of water quality samples that pass through the printed water filter is compared with raw well water samples. The results of laboratory tests of water quality are then analyzed and a conclusion is drawn, how much is the percentage of clarity, the higher the percentage, the higher the water quality. The research target is a printed water filter model that can be applied especially to the Hydraulics Laboratory and a wider target that can be applied by all levels of society, and the clean water supply industry. The advantages of this filter are that it is easy to make by all walks of life, the design is simple and the materials are also easily available wherever we are, whether in the city or in the village. Keywords : Design, Filter, Water, Recycle.